Epidemiology of health risk behavior among university students - Tomires Campos Lopes; Gabriel Gastélum-Cuadras; Artur Luís Bessa de Oliveira; Gabriel El-Corab Esteves; Andréa Carmen Guimarães; João Rafael Valentim-Silva; Estélio Henrique Martin Dantas (Hospital de Clínicas de Itajubá, 2021)
Introduction: Moderate and vigorous physical activity is essential to maintain proper body composition, to reduce the risk of ischemic heart disease, diabetes, and cancer. In addition, it reduces the risk of stroke, hypertension, and depression. Even so, it is an essential determinant of energy expenditure and, therefore, fundamental for energy balance and weight control. Objective: The objective of this epidemiological study is twofold: to quantify and qualify the physical activity of students at the Federal University of Mato Grosso (UFMT) and to compare the level of physical activity of incoming and graduating students. Methodology: The present study used the National College Health Behavior Survey (NCHRBS) questionnaire adapted and validated for use by Brazilian undergraduate students and addressed only aspects related to physical activity. Of the 18,986 students enrolled on UFMT's 5 campuses, 9,720 students accessed the questionnaire. Of these, 7,379 had their answers validated, corresponding to 75.92% of accesses or 38.87% of the universe studied. Results: This study found differences in the level of physical activity among university students, observing less physical activity on the Rondonópolis campus, less physical activity for students in the areas of Linguistics and Letters, when compared with students from other areas, less physical activity in students females when compared to males and less physical activity among freshmen compared to graduates. Conclusion: The study suggest the need for greater investment in policies to promote physical activity among university students in all areas.